Down‐regulation of diesel particulate matter‐induced airway inflammation by the PDZ motif peptide of ZO‐1. Issue 20 (15th September 2020) - Kang, Dong Hee; Lee, Tae‐Jin; Kim, Ji Wook; Shin, Yu Som; Kim, Ju Deok; Ryu, Sung Won; Ryu, Siejeong; Choi, Yung Hyun; Kim, Cheol Hong; You, EunAe; Rhee, SangMyung; Song, Kyoung Seob
Abstract: Although diesel airborne particulate matter (PM2.5) has been known to play a role in many human diseases, there is no direct evidence that therapeutic drugs or proteins can diminish PM2.5‐induced diseases. Nevertheless, studies examining the negative control mechanisms of PM2.5‐induced diseases are critical to develop novel therapeutic medications. In this study, the consensus PDZ peptide of ZO‐1 inhibited PM2.5‐induced inflammatory cell infiltration, pro‐inflammatory cytokine gene expression, and TEER in bronchoalveolar lavage (BAL) fluid and AM cells. Our data indicated that the PDZ domain in ZO‐1 is critical for regulation of the PM2.5‐induced inflammatory microenvironment. Therefore, the PDZ peptide may be a potential therapeutic candidate during PM‐induced respiratory diseases.